2007
DOI: 10.3390/12010060
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Approach to Heterocyclic Building Blocks: Synthesis of Novel Ring Systems Containing a [5,6]Pyrano[2,3-c]pyrazol-4(1H)-one Moiety

Abstract: Abstract:Starting from commercially available educts, a straightforward synthetic route to new heterocyclic building blocks is exemplified with the one-or two-step synthesis of tri-, tetra-, or pentacyclic ring systems. Representatives of the following novel ring systems are prepared from 3-methyl-1-phenyl-2-pyrazolin-5-one and the corresponding o-haloarenecarbonyl chloride using calcium hydroxide in refluxing 1,4-dioxane: pyrimidino [4',5':5,6] While the latter two ring systems are directly obtained due to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 17 publications
0
29
1
Order By: Relevance
“…Specifically, the reaction of 2-pyrazolin-5-ones (tautomers to 5-hydroxypyrazoles [4]) with different o-haloarenecarbonyl chlorides under conditions of the Jensen reaction (calcium hydroxide, refluxing 1,4-dioxane [5]) gave acylated pyrazole intermediates, which were then cyclized with sodium hydride in boiling dimethylformamide to polycyclic compounds (Scheme 1). However, we found that with Nheterocyclic acid chlorides carrying an 'activated' halogen atom in ortho position to the ring nitrogen (derived from 2-chloronicotinic acid, 4-chloronicotinic acid, 3-fluoropicolinic acid, 4-chloropyridazine-3-carboxylic acid, and 3-chloroquinoxaline-2-carboxylic acid) a spontaneous intramolecular cyclization to the target polycycles was observed under Jensen reaction condition (Scheme 1) [1,3]. In contrast, no such behavior was noticed in the reactions of 3-chloroisonicotinic acid chloride and of 5-chloro-2-(methylthio)pyrimidine-4-carbonyl chloride [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the reaction of 2-pyrazolin-5-ones (tautomers to 5-hydroxypyrazoles [4]) with different o-haloarenecarbonyl chlorides under conditions of the Jensen reaction (calcium hydroxide, refluxing 1,4-dioxane [5]) gave acylated pyrazole intermediates, which were then cyclized with sodium hydride in boiling dimethylformamide to polycyclic compounds (Scheme 1). However, we found that with Nheterocyclic acid chlorides carrying an 'activated' halogen atom in ortho position to the ring nitrogen (derived from 2-chloronicotinic acid, 4-chloronicotinic acid, 3-fluoropicolinic acid, 4-chloropyridazine-3-carboxylic acid, and 3-chloroquinoxaline-2-carboxylic acid) a spontaneous intramolecular cyclization to the target polycycles was observed under Jensen reaction condition (Scheme 1) [1,3]. In contrast, no such behavior was noticed in the reactions of 3-chloroisonicotinic acid chloride and of 5-chloro-2-(methylthio)pyrimidine-4-carbonyl chloride [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, we found that with Nheterocyclic acid chlorides carrying an 'activated' halogen atom in ortho position to the ring nitrogen (derived from 2-chloronicotinic acid, 4-chloronicotinic acid, 3-fluoropicolinic acid, 4-chloropyridazine-3-carboxylic acid, and 3-chloroquinoxaline-2-carboxylic acid) a spontaneous intramolecular cyclization to the target polycycles was observed under Jensen reaction condition (Scheme 1) [1,3]. In contrast, no such behavior was noticed in the reactions of 3-chloroisonicotinic acid chloride and of 5-chloro-2-(methylthio)pyrimidine-4-carbonyl chloride [3]. Due to the importance of the N-heterocycle quinoxaline as a structural element in many biologically active compounds [6], even in drugs like Brimonidine (Alphagan™) [7,8], we aimed at the enlargement of our heterocyclic portfolio to include also the new quinoxalino fused skeleton of type 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of a program devoted to the synthesis of new heterocyclic scaffolds we recently presented the synthesis of various heterocyclic xanthone analogues of type A containing a [5,6]pyrano [2,3-c]pyrazol-4(1H)-one substructure ( Figure 1) [1][2][3][4][5][6][7]. In these compounds, one benzene ring of the parent xanthone is replaced by a pyrazole system and the other one by a variable heteroaromatic moiety or by a (substituted) benzene ring.…”
mentioning
confidence: 99%
“…Among the organic compounds, aza-heterocycles such as pyrazole and indazole derivatives, which present considerable biological importance, 1,2 are embedded in a wide range of natural products and medicinal synthetic compounds exerting anti-aggregatory, 3 anti-arrhythmic, 4 muscle relaxing, 5 and anti-diabetic activities. 6 For example, Celecoxib is a pyrazole derivative used as an analgesic.…”
Section: Introductionmentioning
confidence: 99%